Some normal value of coagulation tests, proteins concentration tests, iron concentration and copper concentration tests of local house cats in Baghdad city: Ahmed Numan Al-Ani and Saleem Amin Hasso - Hasso, Saleem Amin (The Iraqi Journal of Veterinary Medicine, 2012)
Forty seven blood samples were collected from local house cats 25 male , 22 female , ranging in age from 1-15 year for both sexes for measuring the following parameters coagulation tests (total Platelets count, Clotting time, Prothrombin Time & Fibrinogen concentration ) and proteins concentration tests (Total protein concentration, Albumin , Globulin concentration ) and iron and copper concentration tests .the results as were follow (228.5 –1,537) X 109Ł , (2-5)min , (6 - 15) sec , (0.5 -4) gŁ , ( 61 - 83 ) gŁ , (23.1 -38.2) gŁ , (25.9-54.2) gŁ , (5.21 – 45.56) μmol/L , (2.29 - 36.52) μmol/L) .the result showed significant differences at level (P<0.05) between the male and female of local house cats in total Platelets count and Prothrombin Time . Other studied parameters showed no significant differences at level (P<0.05) between the male and female in local house cats.